Impact Of Just-In-Time, Total Quality Management And Supply Chain Management On Organizational Performance: A Review Perspective - Mas'udin, Ilyas; Kamara, Mohammed (Jurnal Teknik Industri, 2018)
The purpose of this article aims to examine literary the relationship and practices of Just-in-Time (JIT), Total Quality Management (TQM) and Supply Chain Management (SCM) on firms and their impacts on operational performance, which in turn impact organizational performance. The method used in this work is by gathering information relating to the practices of JIT, TQM, and SCM from different journals and articles based on the survey of various researchers. The source of articles used in this study is popular journal databases such as Google scholar, EBSCO Host, science direct, Emerald, Springer Link and Scopus. From the databases, 65 articles related to those three major operations management components are collected and reviewed. The results showed that JIT, TQM and SCM practices in both manufacturing and service industry individually and jointly impact organizational performance.